Kreativitas dalam Konten Instagram Feeds Produk Kecantikan oleh Studio Postwork - Ratna Tri Maharani (Mahesa Research Center, 2022)
Creating content on social media requires a creative process to support interaction between brands and audiences. Because social media is not only a place to display product catalogs, but also as a marketing medium. The purpose of this study is to explain what the creative process and content design analysis looks like on Wardah's Instagram Feed. This study uses a qualitative descriptive research method. With the aim of this research can explain or describe the design work in detail. The data was obtained by interviewing Taufiqur Rosyadi (27 years old) as the owner of Postwork. Documentation of the design work was obtained through Instagram social media, Wardah's official account. And scientific data obtained from various sources of books and scientific literature. Then data from interviews, photo documentation, and other scientific data as supporting data are processed in detail. Postwork is a creative studio focused on photography and design on social media. One of the clients who use Postwork studio services is Wardah. In the creative process of creating his work, there are 3 stages, namely brainstorming, execution, and editing. The design composition uses the Windows Layout Picture type which emphasizes product figures and headlines.